Somatic copy number alterations by whole‐exome sequencing implicates YWHAZ and PTK2 in castration‐resistant prostate cancer. Issue 4 (12th November 2013) - Menon, Roopika; Deng, Mario; Rüenauver, Kerstin; Queisser, Angela; Pfeifer, Martin; Offermann, Anne; Boehm, Diana; Vogel, Wenzel; Scheble, Veit; Fend, Falko; Kristiansen, Glen; Wernert, Nicolas; et al.
Abstract: Castration‐resistant prostate cancer (CRPC) is the most aggressive form of prostate cancer (PCa) and remains a significant therapeutic challenge. The key to the development of novel therapeutic targets for CRPC is to decipher the molecular alterations underlying this lethal disease. The aim of our study was to identify therapeutic targets for CRPC by assessing somatic copy number alterations (SCNAs) by whole‐exome sequencing on five CRPC/normal paired formalin‐fixed paraffin‐embedded (FFPE) samples, using the SOLiD4 next‐generation sequencing (NGS) platform. Data were validated using fluorescence in situ hybridization (FISH) on a PCa progression cohort. PTK2 and YWHAZ amplification, mRNA and protein expression were determined in selected PCa cell lines. Effects of PTK2 inhibition using TAE226 inhibitor and YWHAZ knock‐down on cell proliferation and migration were tested in PC3 cells in vitro . In a larger validation cohort, the amplification frequency of YWHAZ was 3% in localized PCa and 48% in CRPC, whereas PTK2 was amplified in 1% of localized PCa and 35% in CRPC. YWHAZ knock‐down and PTK2 inhibition significantly affected cell proliferation and migration in the PC3 cells. Our findings suggest that inhibition of YWHAZ and PTK2 could delay the progression of the disease in CRPC patients harbouring amplification of the latter genes. Furthermore, our validated whole‐exome sequencing data show that FFPE tissue could be a promising alternative for SCNA screening using next‐generation sequencing technologies. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.